2007
DOI: 10.1111/j.1530-0277.2007.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Elicited by Affectively Positive Stimuli Is Associated With a Lower Risk of Relapse in Detoxified Alcoholic Subjects

Abstract: In this study, brain activation elicited by briefly presented alcohol-associated stimuli was not associated with the prospective risk of relapse. Unexpectedly, alcoholic subjects displayed increased limbic brain activation during the presentation of affectively positive but not negative stimuli, which may reflect a protective factor in detoxified alcoholic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
83
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 59 publications
15
83
0
3
Order By: Relevance
“…Previous studies have demonstrated differences between controls and alcohol-dependent patients (Heinz et al, 2007;Salloum et al, 2007), and between nonabusing adults with and without a family history of alcoholism (Glahn et al, 2007), in brain regions involved in the processing of emotional stimuli. None of these studies, however, has examined differences among these groups in the effects of acute alcohol administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated differences between controls and alcohol-dependent patients (Heinz et al, 2007;Salloum et al, 2007), and between nonabusing adults with and without a family history of alcoholism (Glahn et al, 2007), in brain regions involved in the processing of emotional stimuli. None of these studies, however, has examined differences among these groups in the effects of acute alcohol administration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prospective neuroimaging studies modelling relapse vulnerability and future drug use have shown that reduced attention toward drug-related cues 11,12,[28][29][30] and increased attention toward non-drug-related reinforcers [31][32][33] predicted longer abstinence durations in individuals with substance use disorders. Although these studies are highly informative, many have been limited to the cross-sectional Background: Increased attention bias toward drug-related cues over non-drug-related intrinsically pleasant reinforcers is a hallmark of drug addiction.…”
Section: Introductionmentioning
confidence: 99%
“…24 Importantly, cross-sectional studies have shown that the LPP amplitude to drug-related cues is decreased 25,26 while that to non-drug-related cues is increased 19,27 after a period of reduced drug use (3 d to about 1 yr). Moreover, prospective neuroimaging studies modelling relapse vulnerability and future drug use have shown that reduced attention toward drug-related cues 11,12,[28][29][30] and increased attention toward non-drug-related reinforcers [31][32][33] predicted longer abstinence durations in individuals with substance use disorders. Although these studies are highly informative, many have been limited to the cross-sectional effects of shorter-term 19 or longer-term abstinence 25,31 relying mostly on self-reported follow-up assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trying to understand these diverging findings, one has to take into account that all studies used different stimuli for craving induction: alcohol-related words (Tapert et al, 2004), alcohol-related pictures with (Myrick et al, 2004) or without (Grüsser et al, 2004) a sip of alcohol ("priming dose"). Furthermore, time point of examination differed from patients being not detoxified (Myrick et al, 2004) to detoxified patients in an inpatient treatment program (Braus et al, 2001;Grüsser et al, 2004;Heinz et al, 2004b;Heinz et al, 2007;Wrase et al, 2002;Wrase et al, 2007).…”
Section: Cravingmentioning
confidence: 99%